Pengaruh Komunikasi dan Motivasi Terhadap Kinerja Karyawan di The Bali Dream Villa Seminyak - Suardiana, I Kadek Andi; Dewi, Desak Made Purnama; Susila, I Made Gede Darma (Universitas Triatma Mulya, 2024)
Employee performance is a crucial element in determining the success of a company, especially in the tourism industry. The effectiveness of communication and work motivation greatly affects the level of performance. Good communication between management and employees can create a harmonious and productive work environment. On the other hand, high work motivation can encourage employees to give their best performance. This study aims to analyze the effect of communication and work motivation on employee performance at The Bali Dream Villa Seminyak. This research was conducted using quantitative methods. The population of this study was all employees of The Bali Dream Villa Seminyak, totaling 59 people. The data collection technique was by distributing questionnaires to all employees. With the help of SPSS 24 with quantitative descriptive analysis and the data was analyzed in multiple linear regression analysis. The results of this study found that communication (X1) has a positive effect of 0.256 with a significance value of 0.000 on employee performance (Y). This shows that increasing communication between employees and management will improve employee performance. Work motivation (X2) also has a stronger positive effect of 0.442 with a significance value of 0.000. Communication and work motivation simultaneously have a significant effect on employee performance, with communication being the dominant variable with a Standardized Coefficients beta value of 0.476 compared to work motivation which has a regression coefficient of 0.421. Several suggestions can be submitted to the management of The Bali Dream Villa Seminyak.